Quality Changes of Pangasius Fillets During Ice Storage - Diah Ikasari; Theresia Dwi Suryaningrum (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2015)
Quality asessment of pangasius (Pangasius hypopthalmus) fillets stored in ice has been conducted. Fish were fasted for one day and slaughtered using bleeding techniques, drained for 10 minutes and filleted in various types of fillet: skin on, skinless, trimmed and untrimmed condition. Fillets were then washed and packed in vacuum plastics, stored in ice (0-4 ºC) for 18 days and observed for its sensory, chemical and microbiological parameters every 3 days. The sensory evaluation was conducted both for fresh or cooked fillets using scoring test on attribute of appearance, odor and texture as well as hedonic test. The chemical parameters observed were proximate; pH and Total Volatile Base (TVB); while microbiological parameter was Total Plate Count (TPC). Results showed that type of fillet did not significantly affect the quality of pangasius fillets. The quality of all treated fillet decreased in line with time of storage, all products were rejected after being stored for 18 days. At the time of rejection, the quality parameters: moisture content ranging from 80.1 to 81.3%, TVB from 11.1 to 11.5 mg N/100g and TPC from 1.41 to 4.6x105 CFU/ml. It is suggested to preserve pangasius fillets in ice less than 18 days.